SOSIALISASI PEMILIHAN KEPALA DAERAH OLEH KOMISI PEMILIHAN UMUM DAERAH (KPUD) KABUPATEN ROKAN HILIR TAHUN 2015 - Siti Kholijah Br. Siregar; M.Y.Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aimed to socialize Regional Head Election By Regional Election Commission (Election Commission) Rokan Hilir year 2015. This study focused on socialization conducted to society in Rokan Hilir on the local elections which took place on December 9, 2015. With the formulation of the problem : How socialization conducted by Regional General Election Commission (Election Commission) Rokan Hilir in local elections in Rokan Hilir 2015. Based on the background of the problem, then this study is to investigate the implementation of socialization local elections conducted by Regional General Election Commission (Election Commission) Rokan Hilir Year 2015. The research method is qualitative. Data collection techniques used Interviews and documentation.The results of the field studies showed that socialization conducted by the Commission of Regional General Election (Election Commission) Rokan Hilir to four target groups consisting of local officials, the organizer of the local elections, community groups, and voters which is not maximized, it is seen from the results of interviews conducted by the author to the target group who get the socialization of the General Election Commission (Election Commission) Rokan Hilir. In the determination of permanent voters list (DPT) seen from the data registered in the election, the reduction in the number of voters and the amount of vote during the elections are also far from the expectations of Regional Election Commission (Election Commission). In addition to the time of election going there some mistakes conducted by the voters, which should not happen because people already get the socialization of the PPK, PPS, KPPS and commission of regional general election (Election Commission) alone how to be a good voter in accordance with the rules that has been established.Keywords: Elections, Political Socialization